Self-Transcendence as a Buffer Against COVID-19 Suffering: The Development and Validation of the Self-Transcendence Measure-B - Wong, Paul T. P.; Arslan, Gökmen; Bowers, Victoria L.; Peacock, Edward J.; Kjell, Oscar Nils Erik; Ivtzan, Itai; Lomas, Tim (Frontiers in Psychology, 2021)
The age of COVID-19 calls for a different approach towards global wellbeing and flourishing through transcending suffering as advocated by existential positive psychology. In the present paper, we first explain what self-transcendence is and why it represents the most promising path for human beings to flourishing through transforming suffering in a difficult and uncertain world. After reviewing the literature of self-transcendence experiences, we conclude that Frankl’s model of self-transcendence is able to integrate both of the characteristics associated with self-transcendence. Then, we discuss how Wong’s self-transcendence paradigm, an extension of Frankl’s model, may to help awaken our innate capacity for connections with the true self, with others, and with God or something larger than oneself. We present self-transcendence as a less travelled but more promising route to achieve personal growth and mental health in troubled times. Finally, we present the history of development and the psychometrics of the Self-Transcendence Measure-B (STM-B) and report the empirical evidence that self-transcendence served as a buffer against the COVID-19 suffering. The present data suggest that the best way to overcome pandemic suffering and the mental health crisis is to cultivate self-transcendence.